A convenient method to pre-screen candidate guide RNAs for CRISPR/Cas9 gene editing by NHEJ-mediated integration of a 'self-cleaving' GFP-expression plasmid. (30th June 2017) - Tálas, András; Kulcsár, Péter István; Weinhardt, Nóra; Borsy, Adrienn; Tóth, Eszter; Szebényi, Kornélia; Krausz, Sarah Laura; Huszár, Krisztina; Vida, István; Sturm, Ádám; Gordos, Bianka; Hoffmann, Orsolya Ivett; et al.
Abstract: The efficacies of guide RNAs (gRNAs), the short RNA molecules that bind to and determine the sequence specificity of the Streptococcus pyogenes Cas9 nuclease, to mediate DNA cleavage vary dramatically. Thus, the selection of appropriate target sites, and hence spacer sequence, is critical for most applications. Here, we describe a simple, unparalleled method for experimentally pre-testing the efficiencies of various gRNAs targeting a gene. The method explores NHEJ-cloning, genomic integration of a GFP-expressing plasmid without homologous arms and linearized in-cell. The use of 'self-cleaving' GFP-plasmids containing universal gRNAs and corresponding targets alleviates cloning burdens when this method is applied. These universal gRNAs mediate efficient plasmid cleavage and are designed to avoid genomic targets in several model species. The method combines the advantages of the straightforward FACS detection provided by applying fluorescent reporter systems and of the PCR-based approaches being capable of testing targets in their genomic context, without necessitating any extra cloning steps. Additionally, we show that NHEJ-cloning can also be used in mammalian cells for targeted integration of donor plasmids up to 10 kb in size, with up to 30% efficiency, without any selection or enrichment.